THE EFFECT OF LAVENDER AROMATHERAPY, BENSON RELAXATION THERAPY, AND A COMBINATION OF BOTH ON ANXIETY LEVELS, SLEEP QUALITY, AND BLOOD PRESSURE IN THE ELDERLY: LAVENDER AROMATHERAPY, BENSON RELAXATION THERAPY - H Wada, Fauziah; Hasiolan, Mara Imbang Satriawan; Andas, Amzal Mortin; Puspitasari, Indah; Prima, Ashar (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: The increasing number of elderly causes various health problems, one of which is hypertension. If hypertension is not well controlled it can cause psychological and physiological problems. The combination of Benson relaxation therapy and lavender aromatherapy is a non-pharmacological intervention that can be used to manage anxiety, sleep quality, and blood pressure. This study aims to determine the effects of lavender aromatherapy, Benson relaxation therapy, and their combination on anxiety levels, sleep quality, and blood pressure in elderly individuals with hypertension. Methods: The research design is quantitative with a quasi-experimental approach without a control group. The sampling selection in this study used purposive sampling. The sample consists of elderly individuals at Sentra Bekasi, totaling 90 respondents, divided into 30 respondents for each intervention. After interventions were carried out and data collected, data analysis was conducted using the MANOVA test. Results: p-value 0.000 indicating a significant effect of intervention type on sleep quality, anxiety, and blood pressure. The next test is the test of between-subjects effects, which shows a significant effect only on the variables of anxiety and blood pressure. The final test used is the Post Hoc Test (multiple comparisons), which indicates that the variables with significant values and a real difference in relation to the intervention are anxiety and blood pressure. Meanwhile, the variable of sleep quality does not show any real difference across each intervention. Conclusion: Overall, Lavender Aromatherapy is superior in reducing anxiety and blood pressure compared to the other two therapies.